Infectious diseases investment decision evaluation algorithm: a quantitative algorithm for prioritization of naturally occurring infectious disease threats to the U.S. military. - Burnette WN; Hoke CH Jr.; Scovill J; Clark K; Abrams J; Kitchen LW; Hanson K; Palys TJ; Vaughn DW; Burnette, W Neal; Hoke, Charles H Jr; Scovill, John; et al. (Military Medicine, 2008)
Identification of the most significant infectious disease threats to deployed U.S. military forces is important for developing and maintaining an appropriate countermeasure research and development portfolio. We describe a quantitative algorithmic method (the Infectious Diseases Investment Decision Evaluation Algorithm) that uses Armed Forces Medical Intelligence Center information to determine which naturally occurring pathogens pose the most substantial threat to U.S. deployed forces in the absence of specific mitigating countermeasures. The Infectious Diseases Investment Decision Evaluation Algorithm scores the relative importance of various diseases by taking into account both their severity and the likelihood of infection on a country-by-country basis. In such an analysis, the top three endemic disease threats to U.S. deployed forces are malaria, bacteria-caused diarrhea, and dengue fever.